Rozwój zrównoważony w gospodarce rynkowej - Graczyk, Andrzej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The aim of the article is to assess the possibilities and ways to implement the idea of sustainable development in a market economy. Economic and social development encounters limitations due to weaknesses and market failures. The concept of sustainable development indicates mainly development goals. Their achievement, however, requires paying attention to the conditions and methods of operation of the entities. Sustainable development will take place under market economy conditions.From the point of view of the neoclassical economics, the basic direction of activities should be creating conditions for the market implementation of sustainable development goals. Institutional economics indicates the need to build a system of norms and values that are appropriate to the idea of sustainable development. Only their dissemination creates conditions for the creation of formal institutions which are the part of the market system. However, it is advisable to combine these methods.The implementation of sustainable development in the management of environmental resources and environmental protection requires increasing the scope of defining property rights and assigning them to specific entities. On this basis, one can create the market mechanisms and expand the scope of market instruments for an environmental protection. Such solutions are consistent with the logic of the market economy and will be understandable as well as acceptable to entities.